Can the use of saline water irrigation reduce the forage deficit in the Brazilian semi arid region? (Research, Society and Development, 2022)
In the Brazilian semiarid, forage production is limited mainly by high evapotranspiration, variability in the temporal distribution of rainfall, low forage support capacity of native pastures (caatingas) and reduced use of technologies for coexistence with droughts, which configure a region with water deficit for most of the year. In this sense, irrigation can contribute to increase the forage supply to the animals throughout the year, especially in the dry season. However, in much of this territory, groundwater and surface water have high saline levels, which can cause soil salinization and make it difficult for forage plants to grow. Understanding the effects of salts present in irrigation water, soil and plants facilitates the management and mitigation of saline levels in soils. In this sense, the objective of this review was to discuss the processes of formation of saline soils, effects of salts on plants and soil, plant tolerance mechanisms and possible management practices that allow the sustainable use of irrigation with saline water in forage plants.